AN ANALYSIS OF USING INDONESIAN LANGUAGE WITH AND WITHOUT CODE-SWITCHING IN ENGLISH DEPARTMENT OF UNIVERSITAS BANDAR LAMPUNG - Ayu Andriyaningsih; Yanuarius Yanu Dharmawan; Gabrielle Ghaniiyyu Nafinoor (Universitas Bandar Lampung, 2020)
This study is qualitative research aiming to analyze the phenomenon of code switching in English DepartmentUniversitas Bandar Lampung. There are two questions in analyzing the phenomenon of code switching usedby the students and teachers. The first question talks about how the use of Indonesian language with codeswitching is and the second question talks about how the use of Indonesian language without code switchingis. The data of this study is gathered by using observation, questionnaires, and interview. As a result, Iconclude that code switching occurs in switching the word, phrase, and sentence level. Switching the code isfrom Indonesian to English and vice versa. The switching also indicates that the speaker wants to emphasisthe point, do not know word in a language, and they are nervous when talking in front of their classmates. Inaddition, without code switching there will be many hesitation and confusion of what is said. Code switchingis one way to help the interlocutor to get into the communication.